Zarząd finansami parafii w późnośredniowiecznej Polsce - Skierska, Izabela (Ecclesia. Studia z Dziejów Wielkopolski, 2013)
The endowment of a church consisted of two funds: dos beneficii (for the use of the parson) and fabrica ecclesiae (for maintenance of the church also in terms of daily liturgy).2 In practice the border between those two spheres of ecclesial assets was not clearly drawn. This occasionally caused problems in the day to day functioning of the church and led to the establishment of secular control of the income of fabrica ecclesiae. In the sources, people appointed to exercise this control are denoted by the following terms: tutores, oeconomi, provisores, questores, viri ecclesiastici, intermittently aedile (edile), but most often vitrici / vitrici ecclesiae, and in German language sources: Kirchenmeister, Kirchenvetter (Kirchenfeter). The institution of the vitrici developed in the West during the 13th century. The vitrici of the parish churches in late medieval Poland become visible in the sources from the beginning of the 14th century, already as an institution well ingrained in the reality of the Polish church. They are in the centre of the author’s attention. Her object is to determine the state of hitherto research, highlight the possibilities of seeking further information, and study this milieu and its activities. The author focuses mainly on material from the Greater Poland area.